Children's mental health and emotional well-being in primary schools - Howard, Colin; Burton, Maddie; Levermore, Denisse; Barrel, Rachel (London SAGE, 2017)
"This new text is written for all those working in primary schools. It supports schools to develop strategies to enhance the importance of mental health and emotional well-being, to work on preventative strategies and to support children when they need more intervention. The text explores what we mean by mental health and well-being."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Child mental health; Emotions in children; Well-being.